Exploring the mechanism of action of Modified Simiao Powder in the treatment of osteoarthritis: an in-silico study - Xu, Zhouhengte; Su, Pingping; Zhou, Xiahui; Zheng, Zhihui; Zhu, Yibo; Wang, Qinglai (Frontiers in Medicine, 2024)
Osteoarthritis (OA) is the most common form of arthritis and the leading musculoskeletal disorders in adults. Modified Simiao Powder (MSMP) has been widely used in the treatment of OA with remarkable clinical efficaciousness. This study aimed to elucidate underlying mechanisms of MSMP in OA by employing network pharmacology, molecular docking, and molecular dynamics simulations, , due to the unclear mode of action.. Bioinformatic analysis was used to evaluate the major chemical constituents of MSMP, determine prospective target genes, and screen genes associated with OA. Network pharmacology methods were then applied to identify the crucial target genes of MSMP in OA treatment. Further analyses included gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. These key targets within the pertinent pathways was further confirmed by molecular docking, binding energy evaluation, and molecular dynamics simulations. Network pharmacology analysis identified an MSMP componenttarget-pathway network comprising 11 central active compounds, 25 gene targets, and 12 biological pathways. These findings imply that the therapeutic effects of MSMP was potentially mediated by targeting several pivotal genes, such as androgen receptor (AR), NFKB1, AKT1, MAPK1, and CASP3, and regulating some pathways, including lipid metabolism and atherosclerosis, the AGE-RAGE signaling pathway in diabetic complications, the PI3K-Akt signaling pathway, fluid shear stress, atherosclerosis, and Kaposi's sarcoma-associated herpesvirus infection. Molecular docking assessments demonstrated that these compounds of MSMP, such as berberine, kaempferol, quercetin, and luteolin, exhibit high binding affinities to AR and AKT1. Molecular dynamics simulations validated the interactions between these compounds and targets. Thus, the therapeutic effect of MSMP likely attributed to the modulation of multiple pathways, including lipid metabolism, atherosclerosis, the AGE-RAGE signaling pathway, and the PI3K-Akt signaling pathway, by the active components such as berberine, kaempferol, luteolin, and quercetin. Especially, their actions on target genes like AR and AKT1 contribute to the therapeutic benefits of MSMP observed in the treatment of OA.